Uji Efektivitas Jamur Entomopatogen Terhadap Larva Penggerek Batang Kelapa Sawit (Oryctes Rhinoceros L.) Di Laboratorium - Alkapi Sukra (Jurnal Riset Perkebunan, 2021)
Oil palm (Elaesis guinensis Jacq.) is a type of plantation/industrial plant in the form of straight- stem trees belonging to the Arecaceae family and Cocoideae subfamily. The horn beetle (Oryctes rhinoceros) is a pest of oil palm stem borer. The aim of the study was to determine the effectiveness of entomopathogenic fungi in controlling the larvae of the oil palm stem borer (O. rhinoceros L.). The study used a completely randomized design (CRD) consisting of 9 designs and 3 replications. The treatments consisted of M0 = control, M1 = M. anisopliae at a dose of 5 g/jar, M2 = M. anisopliae at a dose of 10 g/jar, M3 = M. anisopliae at a dose of 15 g/jar, M4 = M. anisopliae at 20 gr/jar, B1 = B. bassiana at a dose of 5 gr/jar, B2 = B. bassiana at a dose of 10 gr/jar, B3 = B. bassiana at a dose of 15 gr/jar, B4 = B. bassiana at a dose of 20 gr/jar jars. Observational parameters were the mortality percentage of O. rhinoceros larvae and symptoms of attack by O. rhinoceros larvae infected with entomopathogenic fungi. The results showed that the highest percentage of larval mortality of O. rhinoceros was M4 and B4 treatments, namely 100% and 93.33%, respectively, at 12 days of observation. Symptoms of larval death are pale larvae then turn brown or black, after death the larvae will harden like a mummy with a smaller posterior part.